2015
DOI: 10.1118/1.4934373
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tumor‐derived MRI‐texture features for discrimination of molecular subtypes and prediction of 12‐month survival status in glioblastoma

Abstract: The authors evaluated the performance of five types of texture features in predicting GBM molecular subtypes and 12-month survival status. The authors' results show that texture features are predictive of molecular subtypes and survival status in GBM. These results indicate the feasibility of using tumor-derived imaging features to guide genomically informed interventions without the need for invasive biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
99
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(102 citation statements)
references
References 51 publications
3
99
0
Order By: Relevance
“…22,[35][36][37] This study is also related to recent work establishing a link between image features, based on spatial habitats 38 and texture (i.e. fractal texture analysis, histogram of oriented gradients, run length, local binary patterns and Haralick features) 39 and the 12-month survival status of patients with GBM. In comparison with these studies, our analysis focuses on the morphological characteristics of GBM tumours occurring in regions corresponding to necrosis, oedema and active tumour.…”
Section: Discussionmentioning
confidence: 99%
“…22,[35][36][37] This study is also related to recent work establishing a link between image features, based on spatial habitats 38 and texture (i.e. fractal texture analysis, histogram of oriented gradients, run length, local binary patterns and Haralick features) 39 and the 12-month survival status of patients with GBM. In comparison with these studies, our analysis focuses on the morphological characteristics of GBM tumours occurring in regions corresponding to necrosis, oedema and active tumour.…”
Section: Discussionmentioning
confidence: 99%
“…A major reason is that most groups use nonlocalizing biopsies to determine a single representative profile for an entire tumor. 11,[13][14][15][16][17][18][19][20][21] By definition, this does not account for the genetic diversity throughout the various tumor subregions. Also, most biopsies originate from MRI enhancement per routine surgical practice, so tumor profiles from the nonenhancing BAT are typically under-represented.…”
Section: Introductionmentioning
confidence: 99%
“…The textural patterns between voxel intensities and their surrounding neighbors provide further insight to tissue microstructure and the local environment. 11,12 Numerous studies have correlated both MRI signal and texture analysis with genetic profiles in GBM, 5,11,[13][14][15][16][17][18][19][20][21] yet these have been limited in resolving the challenge of GBM's intratumoral heterogeneity. A major reason is that most groups use nonlocalizing biopsies to determine a single representative profile for an entire tumor.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] However, to our knowledge, only two works have studied twodimensional (2D) textural features for outcome assessment. 15,16 METHODS AND MATERIALS Patients This retrospective, three-centre (blinded for review) study was approved by the local institutional review boards (blinded for review). All subjects provided written informed consent at hospital admittance for research and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This fact can be due to the 3D analysis developed, which translates into an averaged nondirectional mapping of tumour heterogeneity, instead of most standard 2D analyses, where different distances or directions lead to different matrices with partial information. 15,16 However, according to Ng et al, 29 whole-tumour analysis was indeed better than single cross-section analysis in separating the Kaplan-Meier survival curve in colorectal cancer, for which they concluded that whole-tumour analysis seems to be more representative of tumour heterogeneity. 30 Moreover, among these texture features, entropy is found again, which reflects the unpredictability of the information content of an image.…”
mentioning
confidence: 99%